A Review Study on Evolution of Human Cognition - Ghanshyam Vatsa, (AG Volumes, 2022)
The purpose of cognitive science is to, as stated in its mission statement, "find the representational and computational powers of the human mind as well as their structural and functional expression in the human brain." Therefore, it is necessary to study the evolution of cognition using evidence of changes in these representational and computational capabilities as well as the little evidence of the functioning of the mind, first from evidence of behaviour (as is the practise of current psychologists), and then from the hazy remnants of the brains of early humans. To make sense of the behaviour evidence preserved in ancient artefacts, such evolutionary research must rely on interpretation. In order to draw any conclusions about cognition, it is necessary to have a well-constructed theory about the interactions between components included within the neurological system, the mental system, and the behavioural system, in addition to a theory about the relationships contained within each of these distinct systems. All of them, plus a convincing explanation for how they relate to the archaeological record, are necessary for drawing conclusions about the development of human thought.